Mitigasi Bencana melalui Pembelajaran IPS Berbasis Ekopedagogi - Pranichayudha Rohsulina; Ferani Mulianingsih (UM Purwokerto Press, 2024)
Social studies learning carried out in junior high schools today does not meet the criteria for ecopedagogy-based learning, especially regarding disaster mitigation. The aim of this research is to analyze the design of social studies learning planning based on eco-pedagogy in disaster mitigation. The method used by researchers is using a qualitative phenomenological approach. The results of this research show that there has been an increase in students' abilities in disaster mitigation through ecopedagogy-based social studies learning. From the research results, it is concluded that through ecopedagogical learning, students' abilities in disaster mitigation through social studies learning can be strengthened and achieve the specified indicators.